Implementasi Metode Weighted Product - Certainty Factor untuk Diagnosa Penyakit Malaria - Yayuk Wiwin Nur Fitriya; Nurul Hidayat; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Malaria is a disease caused by plasmodium parasites. Malaria is spread through mosquito bites that have been infected by the parasite. Malaria symptoms include headaches, high fever, diarrhea, rapid breathing,nausea and vomiting. Malaria can be deadly because it causes damage to heart, kidney and brain damage. So we need a system application to diagnose malaria. It is expected this application can help people or users to get an initial diagnosis as a doctor's referral. In this application the user selects the yes or no buttons for the parameters of malaria symptoms. The data that the user entered is then processed using an algorithm of weighted product and certainty factor to generate early diagnosis type of malaria. In this method there are 22 criteria used and 4 types of malaria. Based on test cases the results accuracy level obtained the test results of an average accuracy of 84%. Accuracy values ​​are derived from 5 test scenarios with different data variants indicating the application was works properly.